2010
DOI: 10.5251/abjna.2010.1.5.737.739
|View full text |Cite
|
Sign up to set email alerts
|

influenza monitoring among birds in Kostanaiskaya Oblast, Republic of Kazakhstan

Abstract: Epizootological monitoring of avian influenza (AI) occurrence in Kostanaiskaya oblast of Kazakhstan was conducted. The staff of the laboratories of the Research Institute for Biological Safety Problems carried out the research in virus isolation from the materials sampled from wild and domestic birds in Kostanaiskaya oblast with use of double blind passage in chicken embryos (CE), hemagglutination test, polymerase chain reaction and electron microscopy. The laboratory studies resulted in detection of an AI vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Mouse and ferret models are widely used for studies of the pathogenicity of avian influenza viruses in mammals, and their use can usually help to predict the pandemic potential of such viruses and aid in the design of advanced methods for prevention and potential treatment of pandemic influenza virus H5N1 infections [16,[27][28][29][30][31][32][33][34][35]. We examined the protective effect and safety of Kazfluvac ® containing different amounts of antigen in ferrets and mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse and ferret models are widely used for studies of the pathogenicity of avian influenza viruses in mammals, and their use can usually help to predict the pandemic potential of such viruses and aid in the design of advanced methods for prevention and potential treatment of pandemic influenza virus H5N1 infections [16,[27][28][29][30][31][32][33][34][35]. We examined the protective effect and safety of Kazfluvac ® containing different amounts of antigen in ferrets and mice.…”
Section: Discussionmentioning
confidence: 99%
“…The protection provided by influenza vaccines is based on the induction of virus-neutralizing antibodies, mainly against the surface hemagglutinin protein [20,31]. Previous studies have indicated that adjuvant-based vaccines possess a higher level of immunogenicity than non-adjuvant-based ones [34][35][36][37][38]. The adjuvant used in Kazfluvac ® is aluminum hydroxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation